A Realização de Initial Coin Offering no mercado de capitais brasileiro - Alves, Rebeca de Barros (2022)
This paper will address legal and regulatory issues related to Initial Coin Offering considering current Brazilian and international regulations, examining the necessary concepts for a complete understanding of the topic, such as cryptocurrencies, securities and the procedures related to this type of offering, including recent regulatory advancements of the agencies and autarchies responsible for the matter. For this analysis, the different types of tokens will be covered, and which are relevant to the legal and regulatory issues in the country. Besides that, in order to fully understand the subject, basic concepts related to the financial market will also be addressed, such as the capital market structure, competence and attributions of each of its agencies and autarchies, all of them of summary understanding for the analysis of the aforementioned theme. From this study, the objective is to question whether the current legislation would be able to regulate the challenges related to ICOs. The intention is to point out possible legislative incapacities and gaps that prevent token public offerings from being conducted diligently and safely in the market, enabling an alternative – and increasingly present in the market – way of raising financial resources by the most varied types of vehicles. By applying deductive methods and bibliographic and documental research, this work aims to analyze the legal framework in force in Brazil, as well as international trends and their respective regulators